Ontogeny and Phylogeny of the Vertebrate Heart - Sedmera, David; Wang, Tobias; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
This book is a compilation of reviews on important aspect of cardiovascular function in vertebrates, and includes ontogenetic development in several of the major animal groups. While emphasis is placed on vertebrates, McMahon reviews the evolution and design of various invertebrates and demonstrates the many analogies on regulation of the cardiovascular systems between multicellular animals. The stunning morphology of the teleost heart of reviewed by Icardo to provide a link between structure and function, paying special attention to the outflow tract and its further evolution. More functional aspects of cardiac function in fish are covered by Tota and Garofalo, including genetics, adaptive growth and regeneration of the fish heart with emphasis on NO signaling between the endocardium and the myocardium. With outset in the variety in form and function of the piscine heart, Farrell, Farrell, Jourdan and Cox provide a novel synthesis on the co-evolution of cardiac performance and the metabolic requirements of the ventricle. The functional correlates of the increased cardiovascular performance within terrestrial vertebrates, particularly the high blood pressures and heart rates of the endothermic birds and mammals, are dealt with in two subsequent chapters. Gillis reviews the evolution of molecular and cellular functions of contractile proteins of the heart, while Galli and Shiels summarizes current knowledge on the conservation in the basic principles of excitation-contraction coupling, in spite of large intra-specific differences in both structure and function of the sarcoplasmic reticulum. Turning to similar functional questions, Sedmera and Ostadal cover the development of cardiac pumping function, conduction and metabolism in higher vertebrates from both clinical and adaptive perspectives, while Wong, Moorman and Barnett provide an extensive review of the early phases on cardiac development of the four-chambered mammalian heart paying a particular attention to its growth, electrophysiological properties and formation of the conduction system. Finally Hicks and Wang provides a provocative view on age-old question on design and function of the reptilian heart.
Comparative evolution and design in non-vertebrate cardiovascular systems -- The teleost heart: A morphological approach -- Fish Heart Growth and Function: From Gross Morphology to Cell Signalling and Back -- A perspective on the evolution of the coronary circulation in fishes and the transition to terrestrial life -- The sarcoplasmatic reticulum in the vertebrate heart -- Evolution of the regulatory control of the vertebrate heart: the role of the contractile proteins -- Ontogenesis of myocardial function -- Basic Cardiac Development: The heart and its electrical components -- The Functional Significance of the Reptilian Heart: New Insights into an Old Question.
Keywords: Life sciences; Medicine; Human physiology; Cardiology; Developmental biology; Evolution (Biology).; Animal Physiology; Life Sciences; Animal Physiology; Human Physiology; Developmental Biology; Biomedicine general; Cardiology; Evolutionary Biology